2009
DOI: 10.1103/physreve.79.061111
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of hard spheres inside hard cylindrical pores

Abstract: Isothermal-isobaric simulations on the ordering behavior of hard spheres upon confinement are presented. The radii of the confining cylinders go from 1.1 to 2 in units of the diameters of the hard spheres adsorbed. In all the range of pressures considered the spheres were located in concentric layers, as many as the radius of the hard cylinder would permit. When the pressure increases, the hard spheres go from being loosely arranged to the formation of ordered structures. This change is marked in all cases by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…It is easy to show that equation (6) gives ψ 0 = 1/ √ W and λ 0 = exp(−βP xx W D)/(βP xx D) for the squares and the relation between the pressure and the Gibbs free energy gives back the Tonks equation for the pressure, which is βP xx W = ρ/(1 − ρD). From the equation of transverse pressure (9) we get that the squares behaves as an ideal gas between the two walls, i.e. βP yy = N/(LW ).…”
Section: Resultsmentioning
confidence: 99%
“…It is easy to show that equation (6) gives ψ 0 = 1/ √ W and λ 0 = exp(−βP xx W D)/(βP xx D) for the squares and the relation between the pressure and the Gibbs free energy gives back the Tonks equation for the pressure, which is βP xx W = ρ/(1 − ρD). From the equation of transverse pressure (9) we get that the squares behaves as an ideal gas between the two walls, i.e. βP yy = N/(LW ).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 For example, with reducing the pore-size, the first order thermodynamic fluid-solid phase transition may completely vanish. 3,4 The confined colloidal system can behave like the one-dimensional Tonks gas in the limit when the particles are not allowed to pass each other (single-file fluid condition). 5,6 Furthermore, the reduction of the spatial dimensions has substantial impact on the diffusion properties of the colloidal systems.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] In slightly wider pores, where the singlefile fluid condition is not satisfied, it was found that a densityjump occurs between fluid-and solid-like structures at the freezing. 3,4 In this work we apply the transfer-matrix method 30 to determine the longitudinal and transversal pair correlation functions of hard core-fluids in such a narrow pore that only nearest neighbor interactions are allowed. The results of the transfer-matrix method are compared with our Monte Carlo simulation data.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is attributed to the entropic dominance on the system, that particles spontaneously move to the more accessible space to maximize the entropy of the system. In the narrow pore, which can hold only one layer of particles at a plane perpendicular to the z direction, the at- tractive force has little impact to the radial density profile and the behavior of ͑r͒ is similar to that of hard sphere systems confined in hard pores discussed by DuranOlivencia et al 16 Similar behavior was also observed in D = 2.5, as seen in the g͑z͒ function shown in Fig. 11, where three peaks are observed at z Ͻ 1.0 at = 0.80, 0.83, and 0.85 indicating a twisted helical structure, and disappear at = 0.90 and 0.95, where the structure is transformed to a square shape consisting of four particles sharing the same z against another nearest square layer by rotating an angle of / 4.…”
Section: Resultsmentioning
confidence: 79%
“…[16][17][18][19][20] The structure of the confined fluids is highly dependent on the pore diameter and it seems there is no simple and continuous dependence, which can be generalized. Here we especially focus on the narrow pores, which can only hold one cylindrical layer of particles, and those are of great theoretical and experimental interest, as in such systems the particles can be self-assembled to form single helical or twisted helical structure.…”
Section: Introductionmentioning
confidence: 99%